Targeted next-generation sequencing identified ADAMTS5 as novel genetic substrate in patients with bicuspid aortic valve. (1st February 2018) - Lin, Xiaoping; Liu, Xianbao; Wang, Lihan; Jiang, Jubo; Sun, Yinghao; Zhu, Qifeng; Chen, Zexin; He, Yuxin; Hu, Po; Xu, Qiyuan; Gao, Feng; Lin, Yan; et al.
Abstract: Background: Bicuspid Aortic Valve (BAV) is the most common congenital heart disease, affecting > 1% of the general population. Up to date, three genes, NOTCH1, GATA5 and SMAD6, have been linked to the isolated form of BAV. However, potential genetic determinants remain largely unknown in most BAV patients. Material and methods: Targeted next-generation sequencing of 7 BAV candidate genes ( NOTCH1, GATA5, SMAD6, NOS3, ADAMTS5, Alk2 and SMAD2 ) was performed in 32 BAV patients. Additional 35 BAV patients and 238 tricuspid aortic valve (TAV) patients, consisting of 107 patients from the transcatheter aortic valve implantation (TAVI) registry and 131 patients from the coronary artery disease (CAD) registry, were selected for further genotyping. Results: We found 2 rare non-synonymous variants in 2/7 genes in 3 BAV patients: one was NOTCH1 :c.4297G > A and the other one was ADMTS5 :c.935C > A that shared by two patients. NOTCH1 :c.4297G > A has not been reported previously. ADMTS5 :c.935C > A was predicted to be pathogenic by all applied algorithms. Alignment of protein sequences from all available species revealed that ADMTS5: p.Arg312Leu, produced by ADMTS5 :c.935C > A, is located in a highly conserved region. The minor allele frequency of ADMTS5 :c.935C > A in BAV patients was significantly higher than the matched population in TAV group (0.015 vs. 0, P = 0.048). Conclusion: Our results suggested that ADMTS5 :c.935C > A are potentially associated with BAV. Further studies, such as large sample case-control replication test and functional research, are needed to explore the role of this rare variant in the development of BAV.